Temporal Nitrous Oxide Emissions from Beef Cattle Feedlot Manure after a Simulated Rainfall Event. Issue 4 (1st July 2017) - Parker, David B.; Waldrip, Heidi M.; Casey, Kenneth D.; Todd, Richard W.; Willis, William M.; Webb, Kathleen
Abstract : Nitrous oxide (N2 O) is a greenhouse gas (GHG) emitted from agricultural operations. The objective of this research was to quantify N2 O‐N emissions from simulated open‐lot beef cattle feedlot pens after rainfall. A recirculating‐flow‐through, non‐steady state chamber system consisting of five 1‐m 2 steel pans was designed for quantifying emissions. A lid was placed sequentially on each pan, and headspace air was recirculated between the pan and a real‐time N2 O analyzer, measuring concentrations every 1 s. Air‐dried manure (89.2% dry matter) from a commercial feedlot in the Texas Panhandle was placed in the pans and then 0, 6.3, 12.7, 25.4, or 50.8 mm of water was applied to simulate a one‐time rainfall event. Emissions of N2 O‐N were monitored for 45 d, where two distinct episodes of N2 O‐N production were observed over time. The first N2 O‐N episode had a duration of 10 h and peaked 2 h after rainfall at a flux of 1.0 to 200 mg m −2 h −1 . The second episode had a duration of 40 d and peaked 15 d after rainfall at a flux of 0.06 to 35 mg m −2 h −1 . The second episode accounted for 69 to 91% of the cumulative N2 O‐N emitted over the 45‐d period. Each millimeter of rainfall increased cumulative N2 O‐N emitted by 167.9 mg m −2 ( r 2 = 0.99, P < 0.001). This rainfall vs. cumulative emissions relationship will be useful for modeling annual N2 O‐N emissions from open‐lot beef cattle feedlots, and for assessing the effectiveness of best management practices for reducing feedlot GHG emissions. Core Ideas: A rapid (60 s) method was developed to quantify fluxes of N2 O‐N from manure. In a 45‐d period, there were two distinct N2 O‐N episodes after simulated rainfall. The first N2 O‐N episode peaked 2 h after rainfall, the second 15 d later. The second accounted for ∼80% of total N2 O‐N emitted during the 45‐d period. Each millimeter of rainfall increased N2 O‐N emissions by 168 mg m −2 over 45 d.